Sadness and Loneliness in Adolescents with Physical, Sensory or Health Problems in Low/Middle-Income Countries - Angel Denche-Zamorano; María Ángeles García-Gil; María Mendoza-Muñoz; Sabina Barrios-Fernandez (MDPI AG, 2023)
Feelings of loneliness and sadness are increasing among the global youth, especially in disadvantaged settings. Young people with disabilities from low-income countries may be at greater risk of experiencing such emotions. This study aims to assess the dependence between difficulties/disability and sadness, loneliness and crying for no reason in young people from low- to middle-income countries and to test the risk of experiencing these emotions in young people with different disabilities versus the overall population. A cross-sectional study was conducted based on the Programme for International Student Assessment for Development survey, with 34,604 participants aged 15 years from seven countries: Cambodia, Ecuador, Guatemala, Honduras, Paraguay, Senegal, and Zambia. Dependent relationships were found between difficulties/disabilities and loneliness, sadness and crying. People with disabilities had a higher prevalence of these emotions. The probability of experiencing sadness, loneliness and crying was higher among people with difficulties/disabilities. Young people with disabilities in low-income countries are at a higher risk of experiencing feelings of loneliness, sadness and crying compared to the general population of the same age.